2018
DOI: 10.12717/dr.2018.22.4.297
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Linolenic Acid: It Contribute Regulation of Fertilization Capacity and Subsequent Development by Promoting of Cumulus Expansion during Maturation

Abstract: The objective of this study was to evaluate the effects of alpha-linolenic acid (ALA) during in vitro maturation (IVM) on cumulus expansion, nuclear maturation, fertilization capacity and subsequent development in porcine oocytes. The oocytes were incubated with 0, 25, 50, and 100 μM ALA. Cumulus expansion was measured at 22 h, and gene expresison and nuclear maturation were analyzed at 44 h after maturation. Then, mature oocytes with ALA were inseminated, and fertilization parameters and embryo development we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…PPARα (Calder et al, 2001;Salustri et al, 2004). Our previous study had shown that treatment of ALA during IVM of porcine oocytes enhanced cumulus expansion and reduced several gap junction and FAs metabolism genes (Lee et al, 2018). We expected that suppression of cumulus expansion could influenced to gene expression that are related with FAs metabolism and cumulus expansion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PPARα (Calder et al, 2001;Salustri et al, 2004). Our previous study had shown that treatment of ALA during IVM of porcine oocytes enhanced cumulus expansion and reduced several gap junction and FAs metabolism genes (Lee et al, 2018). We expected that suppression of cumulus expansion could influenced to gene expression that are related with FAs metabolism and cumulus expansion.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, cumulus expansion of porcine oocytes was enhanced by 50 μM alpha-linolenic acid (ALA) during in vitro maturation, and it was correspond with monospermic fertilization and improvement of early embryonic development (Lee et al, 2018). Auclair et al (2013) reported that amount of total lipid in bovine oocytes was lower in denuded oocytes than cumulus-enclosed oocytes and it suggested that role of cumulus layer is closely associated with lipid store and metabolism in oocytes.…”
mentioning
confidence: 98%
“…Therefore, oocytes matured by in vitro are less likely to develop into the blastocyst stage (Gilchrist and Thompson, 2007) and induces higher rates of miscarriage compare with oocytes matured in vivo (Buckett et al, 2008). Accordingly, many studies have investigated the effect of supplements during in vitro oocyte maturation to improve embryonic development competence (Kwak et al, 2012;Lee et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, alpha-linolenic acid (ALA) is one of polyunsaturated fatty acids (PUFAs), present in spermatozoa, oocytes and follicles in mammals (Homa and Brown, 1992). The ALA improved embryonic development through the expansion of cumulus cells essential for maturation in pigs (Lee et al, 2018). In addition, ALAtreated COCs significantly increased the PGE2 concentration in the medium and regulated meiotic arrest at the germinal vesicle (GV) (Lee et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Cumulus expansion can also be used as a predictive indicator of in vitro fertilization outcomes [9][10][11]. erefore, cumulus expansion is an important parameter affecting the maturity of oocytes [12].…”
Section: Introductionmentioning
confidence: 99%